The Role of Cross-Cultural Communication in Addressing Sharia Economic Issues for the Global Expansion of Sharia Businesses - Taufiqurrachman; Sari, Avid Leonardo; Djuhardi, Lidia; Fatmawati, Endang; Gymnastiar, Iman Ahmad (JOM, 2025)
The global expansion of Sharia businesses requires robust cross-cultural communication to address economic and ethical challenges effectively. This study explores the intersection of cross-cultural communication and Sharia economic principles, emphasizing their significance in fostering sustainable growth in global markets. By conducting an extensive literature review, the study identifies common barriers such as language differences, cultural misinterpretations, and divergent ethical frameworks in the dissemination of Sharia-compliant businesses. It highlights strategies for overcoming these challenges, including the adoption of culturally sensitive communication models and the alignment of business practices with Sharia principles. The findings reveal that effective cross-cultural communication not only mitigates potential conflicts but also enhances the acceptance and competitiveness of Sharia businesses globally. This research contributes to a deeper understanding of the role of communication in bridging cultural divides, thereby promoting the ethical and economic values of Sharia businesses. The study underscores the need for stakeholders to integrate intercultural training and digital communication tools into their operations to facilitate global outreach. It also provides practical insights for policymakers and business leaders on fostering collaboration across cultural boundaries. These findings advance both theoretical and practical knowledge, positioning cross-cultural communication as a critical enabler for the global success of Sharia businesses.